Exploring Tiktok App in Learning Speaking Using Role-Play Activities for ESL Learners in Secondary School - Herwanto, Wanda Hijriani (RETAIN : Journal of Research in English Language Teaching, 2022)
This study discusses the use of the TikTok apps as a form of Technology-Enhanced Language Learning (TELL) media in the speaking class of a secondary school in Indonesia. One of the speaking activities that must be mastered by students is role-play. However, learning speaking skills is always difficult for ESL and EFL students because they have less opportunity to practice speaking. From this condition, this study has a research problem: How does the TikTok App affect students' speaking ability? The objective of this study is to reveal how the implementation of TikTok as a learning medium, the benefits and obstacles experienced by students. A qualitative research design was used in this study. The instruments are interviews, observations, and open questionnaires to obtain more in-depth and objective data triangulation. The observation data were analyzed to answer questions regarding the TikTok implementation. The questionnaires and the interview data was then classified, coded, and analyzed. Both were then compared and interpreted to reveal the benefits and obstacles experienced by students. Thus, TikTok was found to be implemented in synchronous and asynchronous class. Students responses to the benefits related to the speaking aspect were also revealed. However, students were experienced obstacles, both technological and non-technical. This study is necessary to gain teacher insight about the TELL, especially the implementation of the TikTok app in secondary school speaking classes, so they can use it properly.